Electrical and Optoelectronic Properties of the Nanodevices Composed of Two-Dimensional Materials Graphene and Molybdenum (IV) Disulfide - Liu, Cheng-Hua (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis focuses on the transport and magneto-transport properties of graphene p-n-p junctions, such as the pronounced quantum Hall effect, a well-defined plateau-plateau transition point, and scaling behavior. In addition, it demonstrates persistent photoconductivity (PPC) in the monolayer MoS2 devices, an effect that can be attributed to random localized potential fluctuations in the devices. Further, it studies scaling behavior at zeroth Landau level and high performance of fractional values of quantum Hall plateaus in these graphene p-n-p devices. Moreover, it demonstrates a unique and efficient means of controlling the PPC effect in monolayer MoS2. This PPC effect may offer novel functionalities for MoS2-based optoelectronic applications in the future.